Karate Kumite: How to Optimize Performance - Book analysis (Revista de Artes Marciales Asiáticas, 2016)
This work reviews the book entitled Karate Kumite: How to Optimize Performance, edited in English by Helmi Chaabane, PhD., in 2015. The book is composed of five chapters and a total of seven authors participate in it. The first chapter, “Performance Analysis in Karate”, analyzes the temporal structure of combat. The second chapter, “Physiological Characteristics of Karate Athletes and Karate-Specific Tasks” describes the cost and contribution of energy systems, cardiovascular response, blood lactate and hormonal response to combat. The third chapter, “Physical Determinants of Karate Kumite”, analyzes the muscular power, maximum strength, acceleration, speed, reaction time and flexibility of karate. The fourth chapter, “Training Load Monitoring”, describes different methods for monitoring the internal load. Finally the last chapter, “Physical and Physiological Assessment”, presents general and specific tests used in karate. The sound research background of the authors, as well as the extensive use of up to date literature, results in a book of high scientific value. In addition, this is a digital, open-access book that can be accessed without restriction. In conclusion, this is a highly recommended book for coaches, practitioners and professionals related to karate.